AVALIAÇÃO ENERGÉTICA, TÉRMICA E LUMÍNICA DE DISPOSITIVOS DE SOMBREAMENTO EM ESCRITÓRIOS - Garcia, Dayan de Loyola; Pereira, Fernando Oscar Ruttkay (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This paper comes to explore some combinations s properties to balance heat gains, daylight admission, thermal comfort, visual discomfort and energy consumption. These variables were evaluated by EnergyPlus 8.8.0 simulations in a side-lit office model with location in two Brazilian cities with different climatic conditions. Results achieved poor reductions in temperature, but good reductions in cooling energy consumption and daylight glare for those devices that have high reflectance and low transmittance. In other hand, it was observed undesirable reductions in daylight availability and increase in lighting energy consumption.